Síntese, caracterização e potenciais aplicações de ZnO, CuO e ZnO/CuO nanoestruturados - Silva, Laís Truzzi (2014)
Nanostructural zinc oxide, copper oxide and zinc/copper mixed oxides were synthesized by a modified sol-gel method, in order to study the morphology, structure and optical, electronic, electrical, catalytic, bactericidal and antileishmanial properties of these materials. The samples were analyzed by FTIR, XRD, TEM, UV-Vis spectroscopy and Raman scattering spectroscopy. The FTIR, RAMAN spectra and XRD data allowed to detect structural changes occurring in the samples when the Zn/Cu content is varied in the oxide. The crystalline structure of ZnO is wurtzite type while CuO is monoclinic. Was observed that less than 1 mol% of Cu2+ ions was added to ZnO lattice in substitution of Zn2+ even considering that Zn2+ and Cu2+ have very near values of ionics radius, showing the presence of a secondary crystalline phase. The average size of the synthesized crystallites was 25 nm, estimated by the Scherrer?s equation, it agrees with the size observed in the TEM images. The optical properties were examined by UV-Vis spectroscopy and the band gap energies were calculated using the Tauc equation and the Kubelka-Munk function. The obtained energies were 3.23 eV for ZnO, 1.30 eV for CuO and for the mixed oxides the energy value decrease as Cu content increase. The electrical measurements showed that ZnO with 1 mol% of Cu sample has a greater resistivity and lower dielectric properties at room temperature when compared to ZnO and CuO. The photocatalytic activity of the oxides was verified with the degradation of methylene blue and methyl orange dye under visible light irradiation. This study revealed that the nanostructured ZnO has higher photocatalytic efficiency compared to other oxides tested (ZnO containing 1 mol%, 10 mol%, 20 mol% of copper and CuO). The bactericidal activity of some oxides synthesized was tested using gram positive (Staphylococcus aureus, Bacillus subtilis) and gram negative (Escherichia coli and Pseudomonas aeruginosa) bacteria, besides a fungus (Candida albicans). Only inhibition of gram positive bacteria was observed. The study of antileishmanial activity showed that 1 mg/mL of nanostructured CuO inhibited completely the growth Leishmania (Viannia) braziliensis